Закономірності одержання нанонаповнених полімерних матеріялів з матрично-фібрилярною структурою - Резанова, Н.М.; Савченко, Б.М.; Плаван, В.П.; Булах, В.Ю.; Сова, Н.В. (Наносистеми, наноматеріали, нанотехнології, 2017)
Досліджено вплив спільної дії нанонаповнювача і компатибілізатора на реологічні властивості, міжфазні явища та морфологію сумішей поліпропілен/співполіамід (ПП/СПА), а також механічні характеристики сформованих із них монониток. Встановлено, що попереднє введення добавок вуглецевих нанотрубок (ВНТ) і поліпропілену зі щепленим малеїновим ангідридом (ППgМА) у розтоп ПП змінює співвідношення в’язкостей та еластичностей волокноутворювального та матричного полімерів у суміші, наближаючи його до одиниці. Це сприяє підвищенню ступеня дисперґування ПП в матриці співполіаміду. Встановлено, що ВНТ і ППgМА у суміші ПП/СПА впливають на закономірності розпаду рідких струменів (мікроволокон) ПП у матриці СПА. Максимальний ефект досягається за одночасної дії нанодобавки та компатибілізатора — поверхневий натяг γαβ падає від 2,36 мН/м для вихідної суміші до 0,99 мН/м для модифікованої. Показано можливість реґулювання матрично-фібрилярної структури екструдатів три- і чотирокомпонентних композицій за рахунок зниження величини γαβ та підвищення стабільности ПП-мікроволокон. В нанонаповнених компатибілізованих сумішах процес волокноутворення ПП у матриці СПА поліпшується — середній діяметер мікроволокон зменшується від 2,6 мкм (для вихідної суміші) до 1,5 мкм, збільшується їхня масова доля, різко знижується число плівок. Модифіковані суміші характеризуються підвищеною здатністю до поздовжньої деформації, порівняно з вихідною, що забезпечує стабільну переробку їх у волокна та плівки на чинному обладнанні. Максимальну міцність і стійкість до деформації мають мононитки, сформовані із чотирокомпонентних систем, що зумовлено утворенням найбільш досконалої морфології, наповненням вуглецевими нанотрубками, ростом адгезії між компонентами на межі їх поділу. Исследовано влияние совместного действия нанонаполнителя и компатибилизатора на реологические свойства, межфазные явления и морфологию смесей полипропилен/сополиамид (ПП/СПА), а также механические характеристики сформированных из них мононитей. Установлено, что предварительное введение добавок углеродных нанотрубок (УНТ) и полипропилена с привитым малеиновым ангидридом (ППgМА) в расплав ПП изменяет соотношение вязкостей и эластичностей волокнообразующего и матричного полимеров в смеси, приближая его к единице. Это способствует увеличению степени диспергирования ПП в матрице сополиамида. Установлено, что УНТ и ППgМА в смеси ПП/СПА влияют на закономерности распада жидких струй (микроволокон) ПП в матрице СПА. Максимальный эффект достигается при одновременном действии нанодобавки и компатибилизатора — поверхностное натяжение γαβ падает от 2,36 мН/м для исходной смеси до 0,99 мН/м для модифицированной. Показана возможность регулирования матрично-фибриллярной структуры экструдатов трёх- и четырёхкомпонентных композиций за счёт снижения величины γαβ и увеличения стабильности ПП-микроволокон. В нанонаполненных компатибилизированных смесях процесс волокнообразования ПП в матрице СПА улучшается — средний диаметр микроволокон снижается от 2,6 мкм (для исходной смеси) до 1,5 мкм, увеличивается их массовая доля, резко падает число плёнок. Модифицированные смеси характеризуются более высокой способностью к продольной деформации по сравнению с исходной, что положительно влияет на их стабильную переработку в волокна и плёнки на действующем оборудовании. Максимальную прочность и стойкость к деформации имеют мононити, сформированные из четырёхкомпонентных систем, что обусловлено образованием наиболее совершенной морфологии, наполнением углеродными нанотрубками, ростом адгезии между компонентами на границе их раздела. The influence of a joint action of both nanofiller and compatibilizer on rheological properties, interfacial phenomena, and morphology of the polypropylene/copolyamide (PP/CPA) mixtures is studied as well as mechanical characteristics of monothreads formed from these mixtures. As shown, the addition of carbon nanotubes (CNT) and polypropylene with grafted maleic anhydride (PPgMA) slightly reduces the elasticity of melt of the initial PP and increases its viscosity, η; with a joint addition of nanoadditives and the compatibilizer, η is increased by 2 times. Due to this, in modified compositions, magnitudes of ratio of viscosities of fibre-forming and matrix polymers and their elasticities are close to 1 that contributes to better PP dispersion and forming of PP microfibers in the matrix of co-polyamide. As established, the introduction of CNT and PPgMA to the PP/CPA mixture effects on the regularities of decomposition of liquid PP jets (microfibers) in the CPA matrix. The maximum effect is achieved due to a joint action of nanoadditive and compatibilizer—surface tension, γαβ, falls from 2.36 mN/m for the initial mixture to 0.99 mN/m for the modified one. As shown, there is the possibility of regulation of the matrix–fibrillar structure of extrudates for three- and four-component compositions by both reducing the value of γαβ and increasing the stability of PP microfibers. In nanofilled-compatibilized mixtures, the process of fibre-formation of PP in the CPA matrix is improving—the average diameter of microfibers is reduced from 2.6 mm (for the original mixture) to 1.5 mm, their mass fraction is increased, and the number of films is sharply decreased. As found, at simultaneous introduction of modifiers, their synergistic action manifests itself in minimization of both interfacial tension and average diameter of microfibers. The modified mixtures are characterized by the increased ability to longitudinal strain, compared with the original mixture, providing a stable processing into the fibres and films with the active equipment. Maximum strength and resistance to deformation are observed for monothreads formed from four-component systems due to formation of the most perfect morphology, filling with carbon nanotubes, and growth of adhesion between components in the interphase area.